2022
DOI: 10.1080/10717544.2022.2048135
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary delivery of resveratrol-β-cyclodextrin inclusion complexes for the prevention of zinc chloride smoke-induced acute lung injury

Abstract: Smoke bombs are often used in military/fire training, which can produce a large amount of zinc chloride (ZnCl 2 ) smoke. Inhalation of ZnCl 2 smoke usually causes acute lung injury (ALI) that would likely develop to acute respiratory distress syndrome (ARDS). However, there is no effective prevention or treatment strategy for the smoke-induced ALI. Resveratrol (RES) is a natural polyphenol with good anti-inflammatory and anti-apoptotic activities, but its low solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Moreover, the relationship between Th17 cells and Treg cells is inseparable, and Th17 cells can influence the immunosuppressive effect of Treg cells [45]. The Th17/Treg balance is critical in maintaining immune homeostasis, and restoring the Th17/Treg balance can reduce inflammation in ALI [46]. Recent experimental evidence revealed that IL-33 plays a multifaceted role in the development and maintenance of the Th17 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the relationship between Th17 cells and Treg cells is inseparable, and Th17 cells can influence the immunosuppressive effect of Treg cells [45]. The Th17/Treg balance is critical in maintaining immune homeostasis, and restoring the Th17/Treg balance can reduce inflammation in ALI [46]. Recent experimental evidence revealed that IL-33 plays a multifaceted role in the development and maintenance of the Th17 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inhalation therapy using resveratrol as a senomorphic to treat respiratory disease shows that intratracheal administration preserves lung compliance and structure and prevents DNA damage in prematurely aging telomerase null ( terc -/-) mice ( 177 ). In addition, resveratrol-β-cyclodextrin inclusion complexes significantly suppresses ZnCl 2 smoke-induced acute lung injury through anti-inflammatory and anti-apoptotic mechanism ( 178 ).…”
Section: Inhalation Therapymentioning
confidence: 99%
“…A 2% Evans blue (Macklin, E808783) saline solution was prepared, and the tail vein was injected (20 mg/kg). 38 At 30 min post-injection, the mice were anesthetized by intraperitoneal injection of a mixture of 1.25% tribromoethanol and 2.5% 2-methyl-2-butanol. The chest cavity was exposed, and the abdominal aorta was excised.…”
Section: Evans Blue Extravasation Testmentioning
confidence: 99%